Implementasi Merdeka Belajar Melalui Mata Pelajaran Sosiologi di SMA Negeri 2 Tasifeto Barat - Jenabeba Da. C. Pires Belu (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2024)
The purpose of this study was to determine (1) the implementation of independent learning through Sociology subjects at SMA Negeri 2 Tasifeto Barat and (2) To determine the impact of the implementation of independent learning through sociology subjects at SMA Negeri 2 Tasifeto Barat. The type used in this study is qualitative descriptive research, data collection methods using observation, interviews, and documentation. The research subjects were the Principal, Sociology Teachers, and Students. Data validity using source triangulation, technique triangulation, and time triangulation. The results of the study that was carried out at SMA Negeri 2 Tasi Feto Barat show that the implementation of independent learning can be done by designing diverse learning experiences, building effective relationships with students, and providing relevant learning resources. The positive impacts that arise are increased learning independence, the growth of an attitude of independence, the formation of collaboration and communication, and students feeling freer and more independent in learning. While the negative impacts of independent learning are that there are still students who do not understand independent learning, there are difficulties experienced by students in learning due to limited references, and lack of student experience in facing the implementation of independent learning. Apart from that, learning can be implemented by designing diverse learning experiences, building effective relationships with students, and providing relevant learning resources.